Biological characteristics of Trichogramma pretiosum and Trichogramma acacioi (Hym.: Trichogrammatidae), parasitoids of the avocado defoliator Nipteria panacea (Lep.: Geometridae), on eggs of Anagasta kuehniella (Lep.: Pyralidae) - Pratissoli,Dirceu (2005)
The objective of this investigation was to study Trichogramma pretiosum and T. acacioi (Hymenoptera: Trichogrammatidae), parasitoids of the avocado defoliator Nipteria panacea (Lepidoptera: Geometridae) on the eggs of the alternative host Anagasta kuehniella (Lepidoptera: Pyralidae) aiming to use them for biological control of this pest in avocado orchards. The cubic model presented better adjustment for duration of the life cycle of T. pretiosum and T. acacioi with the host A. kuehniella which shows that development rate of these species increases with temperature within the range tested. The number of individuals of both Trichogramma species emerged per egg from this host was higher than one. The quadratic model was significant for viability of T. pretiosum and T. acacioi. This parameter was more affected by extreme temperatures and higher emergence rates of adults of both parasitoids species occurred at temperatures of 20, 25 and 30°C.